Influences of Similarities and Dissimilarities of Bargaining Strategoes: A Saudi Arabian and Jordanian Comparison - Zietawi, Mohammad; Sadi, Muhammad Asad (Asian Journal of Empirical Research, 2013)
The Purpose of this paper is to investigate the influence of similarities and dissimilarities of negotiators characteristics on bargaining strategies. The questionnaires were distributed in Saudi Arabian Eastern Region Province and in the city of Amman, Jordan. They were distributed by mail, hard copies and the internet. A link was initiated so that respondents could access it. The data was collected and analyzed using SPSS and necessary statistical models. Statistical tests like means, ANOVA, t-tests, etc were applied. The authors showed the differences in both cultures and business outcomes and discussed their relevance when designing the bargaining strategies. The paper provides literature review for further research. The paper also proposes innovations, interpretation and application of a wide range of theoretical approaches and business methodologies.